Construcción de un prototipo de termo formador matricial para la elaboración de vajilla desechable biodegradable en base a hojas de achira Canna Indica L. - Albán Ruiz, Diana Alejandra (2019)
The design and construction from a prototype of a matrix thermoformed is developed for the production of biodegradable disposable tableware based on achira leaves (Canna Indica L.), at Cotopaxi Technical University. Thermoforming has developed a number of plastic-based disposable tools. This has resulted in large amounts of waste. The problem lies in the lack of availability, a local level of thermoforming machinery for biodegradable materials, which can be integrated into artisanal production. A prototype machine was built to make the thermoforming, which has a male mold and a female mold to shape achira leaves. Includes two resistances for the provision of calories in the molds (110 oC). To achieve the homogeneity of the thermoforming, the pressure (hydraulic sight glass) and the temperature (thermostats) are controlled. The air temperature from 700 oC to 110 oC , the term of four minutes and fifteen seconds, to the date of 27cm of the water column, up to 39cm, achieving a leaf consistency acceptable for our study. The importance of placing the ribs of the leaves externally, placing a layer of egg white between the leaves for pressing. The technical specifications are met through the tests, and the result is obtained at 110 oC, for 5 minutes at a pressure of 39 centigrade in the water window, the leave is able to write, without losing its color, so that to have a tableware in good condition, its final weight must be 5 to 7 grams, for which resistance tests are carried out on different types of food such as water, milk, and warm noodles, and crockery. But he was able to retain the food.